Career self-efficacy and education abroad: implications for future global workforce. Issue 1 (7th July 2020) - Arghode, Vishal; Heminger, Sarah; McLean, Gary N.
Abstract : Purpose: This study aims to explore how career self-efficacy shapes an individual's career decisions and how learning and development interventions, including participation in education abroad, might play a role in career choice. Design/methodology/approach: The authors used the following databases to review the literature on career self-efficacy: Academic Search Premier, Education Resources Information Center and ProQuest. The following key search terms were used in the search: career self-efficacy, career choice and education abroad. The titles of the identified articles were first reviewed for relevance, followed by the abstract, before further review for inclusion suitability. Findings: Findings suggest career self-efficacy plays a vital role in career decision-making, generating interests and deciding career goals. By improving career self-efficacy among college students, career interests can be reshaped. Findings evidence a relationship between education abroad and career competencies and career development. Research limitations/implications: The review offers an invaluable pathway to breed ideas and thoughts about research in the career self-efficacy domain. While education abroad itself may be a useful intervention in the development of a student's career self-efficacy, among other characteristics and skills, a further empirical study is necessary to determine the extent to which this is true. Using or creating an accurate scale for the measurement of career self-efficacy among undergraduate students is critical to determine a reliable and valid measure, as is controlling for potential differences in self-efficacy between students who self-select for high impact endeavors such as education abroad and those who do not. Practical implications: Noting that practices in international education support collaboration between career services offices and study abroad offices, the authors point to the importance of interventions that intentionally and explicitly incorporate the career self-efficacy construct. Originality/value: Findings evidence a relationship between education abroad and career competencies and career development, through research examining connections to career self-efficacy and education abroad is noticeably scarce. The paper explores the above relationship.